High-Efficiency Lentiviral Transduction of Human CD34(+) Cells in High-Density Culture with Poloxamer and Prostaglandin E2 - Uchida, Naoya (Mol Ther Methods Clin Dev, 2019)
Hematopoietic stem cell (HSC) gene therapy is curative for various hereditary diseases; however, high-efficiency transduction in HSCs remains crucial to improve the prospects for hemoglobinopathies. We previously optimized lentiviral transduction in human CD34(+) cells with serum-free medium containing minimal cytokines, allowing efficient transduction (∼50%) and robust xenograft engraftment. In this study, we further improved lentiviral transduction in human CD34(+) cells. High-density culture conditions (4e6/mL) resulted in ∼5-fold more efficient transduction in CD34(+) cells (p < 0.01) compared with standard cell density (1e5/mL). After co-culturing vector-exposed CD34(+) cells with non-transduced CD34(+) cells, high-density culture conditions enhanced lentiviral gene marking in the non-transduced population (p < 0.01) compared with low-density conditions, suggesting that increasing cell-to-cell contact allows more efficient transduction. Two adjuvants, poloxamer 407 (100 μg/mL) and prostaglandin E2 (10 μM), were added to high-density CD34(+) cells, resulting in ∼4-fold more efficient transduction (p < 0.01) without significant toxicity compared with no adjuvant control. In summary, we developed a highly efficient lentiviral transduction method in high-density CD34(+) cell culture with poloxamer 407 and prostaglandin E2, allowing overall ∼10-fold improvement in transduction efficiency and consistently achieving more than 90% transduction and an average vector copy number of ∼10. Our optimized transduction method should improve gene therapy approaches using lentiviral vectors targeting HSCs.